Easy Arthroscopic Transseptal Approach of the Knee - Lampros Gousopoulos MD; Graeme Hopper MD; Yoann Levy MD; Charles Grob MD; Thais Dutra Vieira MD; Bertrand Sonnery-Cottet MD (Video Journal of Sports Medicine, 2022)
Background: The arthroscopic approach to the posterior compartment of the knee is always challenging. This easy arthroscopic transseptal approach allows safe access to the posterior compartment of the knee, avoiding any potential neurovascular injury. Indications: Indications include arthroscopic posterior cruciate ligament (PCL) reconstruction, fixation of avulsion fractures of the tibial attachment of the PCL, arthroscopic posterolateral corner reconstruction, removal of loose bodies from the posterior compartment, PCL cyst removal, ramp repair, and arthroscopic arthrolysis of the posterior compartment. Technique Description: Using a posteromedial portal, a shaver is introduced with the tip in direct contact with the medial side of the septum facing anteriorly, away from the popliteal neurovascular bundle. The scope is then inserted into the posterolateral compartment to visualize the lateral side of the septum while the shaver remains in the posteromedial compartment. The septum is then released until the tip of the shaver is visible. The shaver is then removed and the scope can now be inserted from the posteromedial portal to the posterolateral compartment through the released septum. Results: The transseptal approach can be performed without any additional risk if the shaver remains centrally on the inferior aspect of the septum. Therefore, the risk of iatrogenic injury of the middle genicular artery is minimized. Likewise, with the knee flexed to 90°, there is no risk of damaging the popliteal neurovascular bundle. Having a precise knowledge of the anatomy of the posterior compartment of the knee minimizes any risks of the transseptal approach, avoiding any additional surgical time whilst facilitating the indicated operation. Conclusion: This easy arthroscopic transseptal approach allows safe access to the posterior compartment of the knee, avoiding any potential neurovascular injury.